A comparative life cycle analysis of plastic and paper packaging bags in the Philippines - Biona, Jose Bienvenido Manuel M. (Animo Repository, 2016)
Various cities in the Philippines have started to prohibit the use of plastic bags and packaging materials in favor of paper products for waste disposal and management reasons. This study evaluated the soundness of these initiatives based on life-cycle analysis (LCA) framework. While a number of studies have looked at similar issues in other countries, results may not be entirely valid in the Philippines due to different variations in energy and material supply chain and waste disposal practices and system. Considering the usual products being purchased by a Filipino family and the amount, 12 liter sando bags and 14 liter paper bag capacity were used as the functional units for the research. Comparison of the impact assessment was done by looking into the cradle-to-grave processes of the two bag materials. The study covered disposal to land, air and water effluents and included the global warming, acidification, ozone depletion and human toxicity impact areas. A modified EDIP was used for the life-cycle inventory and results show that out of the four impact factors, three favored the use of plastic bags. Future studies may be done on other impact factors as well as on other bag materials. This study was commissioned by the Department of Environment and Natural Resources (DENR) to aid policy development in waste management in the country. © 2015 IEEE.